Integrating digital tools into ESP teaching: A need analysis of a business English course - Kholis, Adhan; Iryanti, Heni Dwi (LingTera, 2021)
This case study was a preliminary stage of an on-going research and development project on developing a business English textbook integrated with digital tools for students of English Education at Nahdlatul Ulama University of Yogyakarta. It investigated the students' perceived needs on their business English course. To collect the data, a needs analysis questionnaire was administered to the students using Google form including the students' necessities, lacks, and wants for a practical business English course design. Both quantitative and qualitative methods were used to analyse the collected data. It defined the context in which the students would use business English in their future profession. Results showed that (1) the students' English proficiency was still in the middle, (2) The use of English in daily life communication was on occasion, (3) The English skills' preferences should be learnt in the business context were speaking, writing, listening, and reading, (4) Topics included in the business contexts were interview, curriculum vitae, and presentation in the top three, (5) Digital tools' preferences to be integrated into learning were Kahoot, Padlet, and VoiceThread in the top three, and (6) Learning methods implemented were group discussion and project-based learning in the top two.